The effect of telenursing follow-up on blood glycosylated hemoglobin and quality of life in the elderly with diabetes type 2 - Elahe Asadi; Fariba Borhani; Abbas Abbaszadeh (Journal of Education and Health Promotion)
Background: Diabetes mellitus is one of the most common and costly diseases. Telephone nursing plays an undeniable and effective role not only in reducing costs but also in providing nursing care and improving the quality of life of patients. This study was conducted with the aim of investigating the effect of telephone follow-up by a nurse on hemoglobin glycated control and the quality of life of elderly patients with diabetes type 2. Materials and Methods: In this clinical trial study, 90 patients with type 2 diabetes referred to the hospitals affiliated with Shahid Beheshti University of Medical Sciences in 1401–1402 were divided into two control and experimental groups (45 patients in each group) by the simple random sampling method. Data collection tools were a demographic-clinical information questionnaire and an elderly quality of life assessment questionnaire (CASP-19). Before the intervention, questionnaires were completed by the sample. The nursing follow-up test group intervention lasted for 12 weeks. In the first month, participants were contacted twice a week, and in the second and third months, they were contacted once a week by phone. Patients in the control group received only follow-up and center care. Finally, the statistical software SPSS version 21 (SPSS Inc, Chicago IL) was used for data analysis. In this study, an independent sample t-test or Mann-Whitney analysis, paired t-test or Wilcoxon test, and Analyze of Covariance (ANCOVA) test were used based on the type of variable distribution (normal or non-normal). Results: The results of this study showed that by adjusting the variables of weight, baseline level of the quality of life score (before the intervention), age, gender, and physical activity, the difference in the mean changes of the quality of life score in the control and intervention groups in the nurse telephone follow-up intervention was significant (P = 0.054). In addition, the difference in the mean changes of HbA1C in the control and intervention groups was significant due to the nurse’s telephone follow-up intervention (P < 0.001). Conclusion: The findings of this study showed that telenursing training and follow-up in the intervention group improved the quality of life and decreased hemoglobin glycosylate in the elderly with type 2 diabetes. Therefore, telenursing can be effective in improving the quality of life of the elderly with type 2 diabetes and managing its complications.